From Data to Policy Analysis: Tax-Benefit Modelling using SILC 2008 - CALLAN, TIM; WALSH, JOHN; KEANE, CLAIRE (My University, 2010)
Policy makers and the body politic have a strong interest in ensuring that the tax transfer system functions well. This common interest in policies that are efficient in achieving their objectives ? including economic efficiency and fairness ? is heightened by the scarcity of resources during the current crisis. The effects of tax and welfare policy changes are wide-ranging and complex, varying with the characteristics of individuals and their family and household situation. Changes in income tax and social welfare can alter the distribution of income and the incidence of poverty (whether measured in terms of income alone (?risk of poverty?) or in terms of income and material deprivation (consistent poverty)). Tax and welfare changes can also have significant impacts on financial incentives to work, potentially affecting decisions about labour market participation and hours of work.
PUBLISHED
Keywords: Economics; Tax-Benefit Modelling